Ring-type structures in the Planck map of the CMB. Issue 3 (7th November 2017) - An, Daniel; Meissner, Krzysztof A.; Nurowski, Paweł
Abstract: We present the results of the quest for ring-type structures on the maps observed by the Planck satellite. The results show that the vicinity of one radius (γ = 0.14  rad) of the rings is distinguished. Twisting the circles into deformed ellipses gives a pronounced drop of significance with the increase of twisting; however, this behaviour is also present in some statistically isotropic simulations.